LOWER TRAPEZIUS TRANSFER FOR IRREPARABLE ROTATOR CUFF TEAR: SYSTEMATIC REVIEW - Guilherme Trigueiro Alarcon; Jyotis Natacha Brito Corbin; Eduardo Misao Nishimura; Luciano Pascarelli; Eiffel Tsuyosho Dobashi (Acta Ortopédica Brasileira)
ABSTRACT To evaluate functional results considering the final stages of function and postoperative pain in patients with irreparable rotator cuff tears undergoing surgical treatment by lower trapezius transfer. A systematic review of the literature was carried out following the PRISMA guidelines without restrictions on language and year of publication. The search was carried out in the following databases: MEDLINE/PubMed, EMBASE, Scopus and Cochrane Central Register of Controlled Trials. The main descriptors used were: "Rotator Cuff" OR "Rotator Cuff Injuries" OR Rotator Cuff Tear. The stages analyzed were pain, range of motion and function. We found 215 articles, of which 12 were included involving 374 participants. There was a statistically significant improvement comparing the pre and postoperative periods. The average intensity of pain was 7.1 and decreased to 2.4 according to the VAS. Using the ASES system, the result certainly improved, where the initial average was 49.5 (bad result) and the final average was 78.3 (good result). The results suggest that lower trapezius transfer is effective as a therapeutic option in patients treated by the surgical technique studied, according to the results found. Level of Evidence III; Systematic Review.